Environmental risk analysis probability distribution calculations - Theodore, Louis (CRC Press, Taylor & Francis Group, 2016)
Environmental Risk Analysis: Probability Distribution Calculations defines the role that probability distributions play in risk analysis, and gives direction on how to measure and compare the magnitude of risk more efficiently. Designed for the practicing environmental engineer and scientist, this book clearly explains the key fundamentals, principles, and applications of probability distributions in environmental risk analysis